IMPLEMENTASI PENDIDIKAN LINGKUNGAN BERBASIS KERAJINAN GASTROPODA DAN BIVALVIA BAGI ANAK USIA DINI DI KOTA AMBON - Pical, Cyecilia; Hulopi, Mahriyana; Lewerissa, Yona Aksa; Pello, Frederika S; Ayal, Frederik Willem (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2025)
This Community Service (PkM) activity aimed to enhance the ecological awareness and creative abilities of young children in the use of gastropod and bivalve shells. The activity took place at the Moluccas Coastal Care (MCC) Learning House in Ambon City and involved 26 children aged 5–10. Methods included interactive lectures on the ecological and economic benefits of molluscs, training in creating simple crafts such as brooches, bracelets and key chains, and evaluation through question-and-answer sessions and assessment of the children's work. The results showed an improvement in the children's understanding of gastropods and bivalves, as well as an enhancement of their ability to produce creative products from shells. This activity promoted creativity, motor skills and environmental awareness from an early age, while also creating opportunities for the utilisation of shell waste as valuable products.